Discrete-time coordinated control of leader-following multiple AUVs under switching topologies and communication delays. (15th January 2019) - Yan, Zheping; Yang, Zewen; Yue, Lidong; Wang, Lu; Jia, Heming; Zhou, Jiajia
Abstract: The coordinated control of multiple AUVs systems is the key to guarantee the consensus of AUV's motion status. This paper proposes coordinated control protocols with or without time delay for the coordination control problem of multiple AUVs under switching communication topologies based on discrete information. Firstly, the state feedback linearization method is used to convert coupled nonlinear AUV kinematics and kinetic equations into second-order affine forms, and a mathematical model is given in discrete time. Because the leader AUV is equipped with more accurate sensors, the leader-follower type of formation structure is adopted, leader AUV sends status information to followers, and the follower AUVs communicate with themselves randomly. Secondly, the coordination control protocols are designed for the cases of no time delay and time delay, and sufficient conditions for the consensus algorithm are analyzed and given based on the matrix theory. Finally, the correctness of the proposed coordinated control protocols is proved by simulation experiments and the trajectories of multiple AUVs converge to the desired trajectory.